2015
DOI: 10.1039/c5ce01648g
|View full text |Cite
|
Sign up to set email alerts
|

Unique topological motifs in two Cd(ii)-coordination polymers: mutual-embedded 2D bilayers, 3D polythreaded structures, self-penetrated networks and 2D → 2D interpenetrated homochiral bilayers

Abstract: Two unique entangled Cd(ii) coordination polymers have been modulated by flexible/semi-rigid mixed-ligand systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…56,72,460,463 Some recent examples featuring 2D to 2D parallel interpenetration are illustrated here. 496 Similarly, [Mn(NCS) 2 L 2 ] (L = bis(4pyridyl) substituted hydrazone derivatives) with triply interpenetrating corrugated 2D sheets are reported by Batten and co-workers. 497 Nagaraja et al also reported two 2D MOFs with sql net, [Zn 2 (muco) 2 (azopy) 2 ]•3DMF•2H 2 O and [Cd(muco)-(4bpdh)(H 2 O)], based on trans,trans-muconate dianion (muco) and different linkers 4,4′-bisazobipyridine (azopy) and 2,5-bis(4-pyridyl)-3,4-diaza-2,4-hexadiene (4bpdh), respectively.…”
Section: Interpenetrated and Polycatenated Structuresmentioning
confidence: 65%
See 2 more Smart Citations
“…56,72,460,463 Some recent examples featuring 2D to 2D parallel interpenetration are illustrated here. 496 Similarly, [Mn(NCS) 2 L 2 ] (L = bis(4pyridyl) substituted hydrazone derivatives) with triply interpenetrating corrugated 2D sheets are reported by Batten and co-workers. 497 Nagaraja et al also reported two 2D MOFs with sql net, [Zn 2 (muco) 2 (azopy) 2 ]•3DMF•2H 2 O and [Cd(muco)-(4bpdh)(H 2 O)], based on trans,trans-muconate dianion (muco) and different linkers 4,4′-bisazobipyridine (azopy) and 2,5-bis(4-pyridyl)-3,4-diaza-2,4-hexadiene (4bpdh), respectively.…”
Section: Interpenetrated and Polycatenated Structuresmentioning
confidence: 65%
“…Three identical helical chains with the same chirality entangle with the triple-stranded helix of opposite chirality from the adjoining layers. Another 2D sql MOF [Cd­( m -pdoa)­(bpp)­(H 2 O)]·2H 2 O] ( m -H 2 pdoa = 1,3-phenylenedioxy diacetic acid) with unusual homochiral bilayers also display similar interpenetration . Similarly, [Mn­(NCS) 2 L 2 ] (L = bis­(4-pyridyl) substituted hydrazone derivatives) with triply interpenetrating corrugated 2D sheets are reported by Batten and co-workers …”
Section: Different Entanglementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of metal-organic frameworks with intertesting structures have been reported based on 5-hydroxyisophthalic acid as this kind of carboxylate ligand offers six kinds of intricate connection models (Xu & Li, 2014). Supermolecules constructed by mixed ligands including carboxylate ligands and other N-donor molecules often show interesting networks compared with those compounds constructed by a single ligand (Xu et al, 2015). However, there are only a few examples reported which are based on OH-BDC and bib molecules (Wang et al, 2014;Liu & Guo., 2012;Su et al, 2015;Li et al 2015;Guo et al, 2013).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…1) due to their structural complexity and functional properties (Martins et al, 2017;Gong et al, 2016;Shi et al, 2014;Yang et al, 2009Yang et al, , 2014Wu et al, 2011;Wang et al, 2007Wang et al, , 2008Liao et al, 2006). The favourite strategy for this issue is the use of conformationally kinked flexible ligands (Xu et al, 2015;Kim et al, 2014;Zhou et al, 2012;Wang et al, 2011;Hou et al, 2010). However, most of the designed entanglements fall into the interpenetrating category and only a few target nets were obtained unexpectedly.…”
Section: Introductionmentioning
confidence: 99%